A Systemic Functional Linguistics (SFL) Analysis on Short story Cindelaras by Cerita Rakyat from East Java - Harahap, Risma Sabrina; Tifani Angrayani; Rafli Firmansyah Putra; Edi Suprayetno (English Lecturers and Teachers Association (ELTA), 2024)
The purpose of this study was to analyze practical literature with a systemic functional linguistics approach. The ideal, textual, and interpersonal meanings will be analyzed using the short story “Cinderaras” by Cerita Rakyat from East Java. The researchers used descriptive qualitative methods. The stories were divided into sections and analyzed into tables using Systemic Functional Linguistics (SFL). The result of ideational metafunction analysis showed that most of the text used material and verbal processes which reached the value of 33,33%, behavioral processes reached the value of 22,22% and the last was 11,11% of behavioral processes. The result of textual metafunction analysis showed that 83,33% were topical unmarked themes and 16,66% were topical marked themes. In other words, it can be said that the “Cindelaras” was simple and concise and focused on actions and events and how the characters communicate, speak, or interact with each other. Keywords: systemic functional linguistics; short story